2016
DOI: 10.2166/wst.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Rapid novel test for the determination of biofouling potential on reverse osmosis membranes

Abstract: A novel method was proposed to determine biofouling potential by direct analysis of a reverse osmosis (RO) membrane through fluorescence intensity analysis of biofilm formed on the membrane surface, thereby incorporating fouling tendencies of both feedwater and membrane. Evaluation of the biofouling potential on the RO membrane was done by accelerated biofilm formation through soaking of membranes in high biofouling potential waters obtained by adding microorganisms and glucose in test waters. The biofilm form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Meanwhile, the study of [37] suggested some testing sets to allow for the determination of the water samples capacity of microbial support. In addition to using fluorescence intensity microplate analysis to determine biofouling potential on RO membranes [35,37,38].…”
Section: Biofouling Potential Indicators and Measurementsmentioning
confidence: 99%
“…Meanwhile, the study of [37] suggested some testing sets to allow for the determination of the water samples capacity of microbial support. In addition to using fluorescence intensity microplate analysis to determine biofouling potential on RO membranes [35,37,38].…”
Section: Biofouling Potential Indicators and Measurementsmentioning
confidence: 99%